Gender Balance in Construction Material Research: The Analysis of Alkali-Activated Materials by a Bibliometric Study Using Scopus Database - Masi, Giulia; Manzi, Stefania; Bignozzi, Maria Chiara (Frontiers in Materials, 2020)
Research in alkali activated materials (AAMs) is an innovative and dynamic Material Science topic. This is due to the relevant performances in terms of physico-mechanical properties comparable to traditional construction materials (e.g. ordinary Portland cement). The sustainability of AAMs are often highlighted since they can be developed by using many natural or industrial by-products-based precursors. The leads to challenges with the optimization of AAMs production, due to their different performances, availability, and costs. However, they are flexible and locally adapted materials. The research interest on AAMs has rapidly increased in the early 2000s. In recent years, about 1000 international papers have been published each year. This study aims at assessing the gender balance of this specific research topic to investigate the relevance of women participation. Author lists of the published papers were analyzed throughout SCOPUS database, applying “alkali activated material” and “geopolymers” as keywords in the titles, abstracts, and keywords search. The last 10 years (2009 – 2019) were taken into account. The gender of the most prolific authors was analyzed and a focus of European authors on this topic was considered, as more than 25% of the research in AAMs has been carried out in Europe. The analysis of 5900 papers in the last decade shows that there is currently a shift toward men in the gender balance in this specific research and female authors only covered 22% of the most productive authors worldwide. Considering European authors, a more equal gender distribution is reached, when the first author is considered, with a concentration of women in the range of 36-56%, recorded over 1396 papers.